Transportation Systems Analysis and Assessment 2020
DOI: 10.5772/intechopen.88929
|View full text |Cite
|
Sign up to set email alerts
|

Railway Infrastructure Capacity in the Open Access Condition: Case Studies on SŽDC and ŽSR Networks

Abstract: The railway sector in the European Union is changing. The goal of EU transport policy is to liberalize the market for rail transport services, dismantle national transport monopolies, and open competitive public tenders to other train operators. For the optimal utilization of the railway infrastructure capacity, it is necessary to calculate it properly in terms of open access to the infrastructure. At present, many important corridors are at full capacity. Therefore, in order to increase the number of freight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…Our study has observed that railway infrastructure significantly varies from station to station due to differential spatial organisations. Similar kind of result has been found in the work of Palin et al (2021), Besinovic (2020), Gašparík and Cempírek (2019), Funk et al (2019), Gasparik et al (2018), Kasraian et al (2016), , Lindfeldt (2015), Debrezion et al (2007). After critical discussion on the findings it can be asserted that comparatively less complex physio-environmental location has relatively better railway infrastructure.…”
Section: Discussionsupporting
confidence: 87%
“…Our study has observed that railway infrastructure significantly varies from station to station due to differential spatial organisations. Similar kind of result has been found in the work of Palin et al (2021), Besinovic (2020), Gašparík and Cempírek (2019), Funk et al (2019), Gasparik et al (2018), Kasraian et al (2016), , Lindfeldt (2015), Debrezion et al (2007). After critical discussion on the findings it can be asserted that comparatively less complex physio-environmental location has relatively better railway infrastructure.…”
Section: Discussionsupporting
confidence: 87%
“…The travel time is directly proportional to the vehicle's output (class Eem 923: 1 500 kW in electric mode, conventional diesel locomotive: ca. 700-800 kW) [8,9].…”
Section: Selected Other Options For Deployment Of Hybrid and Dual Loc...mentioning
confidence: 99%
“…On defined lines with international freight traffic, a line category with a weight per axle of 25t is required, but to increase their performance, raising the limit up to 30t is being considered. The existing maximum length of freight trains of 650 m will be extended to 850 m. This will promote greater efficiency in rail freight transport [10,11].…”
Section: Transport Performance By Individual Transport Modesmentioning
confidence: 99%